The Universality of Wisdom and the Signs of the Times: On the Friendship Between Stefan Swieżawski and Jacques Maritain - Grzybowski, Jacek (Roczniki Filozoficzne, 2025)
The article focuses on the meeting and friendship of two European philosophers, Jacques Maritain and Stefan Swieżawski. They proved extremely fruitful especially for Swieżawski, who, as a Polish historian of philosophy, educated several generations of students and scholars in the 20th century. Both thinkers were united by the love of wisdom, faith, concern for the future of culture, as well as the role and tasks of the Church in the ever-changing world. The enduring bond of this special meeting, a long relationship and, as they themselves said, friendship, was grounded in their love of and search for truth, both in philosophy (especially in the texts of St. Thomas Aquinas) and in the community of faith. Both wanted to build a culture of wisdom, philosophical reflection, even contemplation. They realized how much evil had happened in the 20th century and how many tragic events had resulted from ignorance, absence of dialogue, and disregard for the rational education of young generations. A closer look at the lives and works of these two men can help us understand the universal principles of the formation of culture. This is all the more necessary today, in the early 21st century, when we are facing challenges of globalization, digitalization and technologization of almost all spheres of life. Indeed, philosophical reflection on the mystery of being and the role of ethics in culture is still relevant.